(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Benserradj O, Benslama O, Ghorri S. 2021. Insights into the genome sequence of the glyphosate-degrading bacterium Enterobacter sp. Bisph1. Biodiversitas 23: 817-882. Glyphosate is by far the most extensively utilized herbicide in the world, and because of its negative effects on the environment and animal health, finding microorganisms with the ability to degrade this herbicide is one of the scientists’ top priorities. Enterobacter sp. Bisph1 was isolated during prospecting glyphosate-degrading bacteria from a sandy soil of the region of Biskra in Algeria. To better understand the involvement of this strain in the degradation of glyphosate, a sequencing of the 4.5 MB genome of Enterobacter sp. Bisph1, as well as an annotation, and analysis of its genome sequence were performed in this study. Genomic DNA was sequenced on a MiSeq sequencer llumina using paired-end sequencing with the Nextera XT protocol. The genome of strain Enterobacter sp. Bisph1 comprises one chromosome of 4,578,487 bp with a GC content of 53.6%. Its 4,330 genes (78.13%) were assigned a putative function. The genome contains two intact phages and no CRISPR was found. The genome inspection also revealed the presence of the carbon-to-phosphorus (C-P) bond lyase coding genes clusters that consists of eight genes phnFHIJKLMP. The draft genome of the Enterobacter sp. Bisph1 provides insight into the role of this strain as an important agent of bioremediation of glyphosate by examining the genes known to encode the biodegradation enzymes of this herbicide. The sequencing of the genome of Bisph1 allows a better understanding of the taxonomy of this strain within the Enterobacteriaceae family.